Buying happiness: How brand engagement in self‐concept affects purchase happiness. Issue 11 (28th July 2022) - Razmus, Wiktor; Grabner‐Kräuter, Sonja; Kostyra, Martyna; Zawadzka, Anna Maria
Abstract: In general, experiential purchases have been found to make people happier than material purchases. However, previous research has ignored a crucial issue—the importance of the brand and the consumer−brand relationship in this context. Since many purchases are associated with a brand and the brand is often the main motivation for the purchase, we argue that researchers should include the consumer−brand relationship in studies on the effects of material versus experiential consumption on happiness. Building on the social exchange theory, the current research examines the moderating role of consumers' tendency to include brands as part of the self in the relationship between purchase type and happiness. Across three studies, using different methods (a comparative survey: N 1 = 422 individuals; two experiments: N 2 = 206 and N 3 = 177 individuals), we found that individuals with high levels of brand engagement in self‐concept (BESC) derive similar levels of purchase‐related happiness from experiential and material purchases, while individuals with low levels of BESC find more purchase‐related happiness in experiential than in material purchases.